PENGARUH KAMPANYE #UBAHJAKARTA OLEH PT MRT JAKARTA TERHADAP NIAT PENGGUNA TRANSPORTASI PUBLIK DI JAKARTA - Muhammad Yusuf Kemal; Niken Febrina Ernungtyas (Universitas Bina Sarana Informatika, 2020)
The direction of transportation development which is triggered by traffic density due to population growth and the dynamics of big cities tends towards the mass rapid transport (MRT) system. Jakarta as a megapolitan city with the highest traffic congestion in the world. One of the modes of public transportation, the Jakarta MRT, is carrying out the #ubahjakarta campaign to encourage people to switch from private vehicles to public transportation. This campaign has been going on since August 2018, but there has never been any research specifically measuring the #ubahjakarta campaign, so this study analyzes based on exposure, positive response to cognitive, positive response to attitude, positive to behavior, cognitive to intention, attitude to intentions, behavior to intentions, personal norms to intentions, social influence to intentions. The research method uses a quantitative approach by conducting an online survey of 86 respondents in a descriptive manner. Data analysis uses univariate analysis for demographic data. While testing the hypothesis using a simple regression test. There are seven hypotheses tested in the study and not all are statistically proven. This research shows the intention to switch from private vehicles to public transportation. The results are based on the results of the validity test showing the value of the Positive Response To Cognitive variable of 0.779 (significant = 0.768), and based on the results of the Social Influence regression test on Intention with a value of R = 0.543 (sig = 0,000).